Prognostic potential of amniotic fluid analysis at birth on canine neonatal outcomes. Issue 3 (December 2015) - Groppetti, D.; Martino, P.A.; Ravasio, G.; Bronzo, V.; Pecile, A.
Highlights: The prognostic value of amniotic fluid analysis at the time of birth in dogs was considered. High amniotic lactate and cortisol concentrations were found in stillborn pups. Amniotic glucose concentrations were low in stillborn pups. Amniotic glucose, lactate and cortisol concentrations were related to the type of parturition. Abstract: Glucose, lactate and cortisol concentrations in amniotic fluid were measured at birth in 95 pups and related to neonatal viability based on Apgar scoring and to neonatal mortality. Neither amniotic parameters nor neonatal mortality were associated with the Apgar score. Stillborn pups showed high lactate ( P < 0.001) and cortisol ( P < 0.05) but low glucose amniotic concentrations ( P < 0.001). No amniotic fluid differences were observed between normal and malformed pups. Amniotic glucose ( P < 0.001), lactate ( P < 0.05) and cortisol ( P < 0.05) concentrations were higher in pups delivered by vaginal parturition than by Caesarean section. Birth weight was higher in live pups than in pups dying within 48 h ( P < 0.05). Although these are preliminary results, the analysis of amniotic fluid collected at birth could be a valuable predictor of neonatal outcomes in dogs.